Designing PMRI-Based Learning Materials Using the ADDIE Model to Enhance Conceptual Understanding of π (Pi) in Circle Topics - Muhammad Assegaf Baalwi; Wahyu Maulida Lestari; Masyitah Noviyanti (Universitas Pendidikan Mandalika, 2025)
This article is about developing mathematics learning materials related to the Indonesian Realistic Mathematics Education (PMRI) approach for teaching the circle topic, with a focus on enhancing sixth-grade students’ conceptual understanding of π (Pi) at MI Ma’arif Pagerwojo. The development followed the ADDIE instructional design model. The research instruments included expert validation sheets, lesson implementation observation sheets, response questionnaires, and achievement tests. Based on expert validation, two validators rated the teaching module at 95.5% and 92.6%, the student worksheet (LKPD) at 91.6% and 94%, and the learning outcome test at 85% and 90% all falling within the